A study of skin diseases in Tunis - Souissi, Amel (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2007)
Background: Epidemiological studies of skin diseases are rather rare. Most of them are based on hospital attendance. The aim of this study was to determine the spectrum of skin diseases in the Tunis region. Methods: This prospective study encompasses consecutive patients attending a number of public or privatedermatological outpatient clinics in Tunis from June 1999 to July 2000.Diagnosis was mainly based on clinical findings, but supplemented by further investigations when needed. Results: The total number of patients was 28,244, with 28,515 pathological conditions reported. The mean age was 31.6 years with a M/F sex ratio of 0.82:1. Infections constituted the major group of disorders (38.6%), followed by hair follicle and sebaceous gland diseases (14.3%), allergic skin diseases (13.6%), and tumors (7.8%). Infectious diseases included fungal (16.38), viral (9.9%), and bacterial (9.24%) conditions. Dermatitis accounted for 9.9% of cases and acne for 6.9%. Tumors were mainly benign (7%) and very rarely malignant (0.5%). Conclusions: The survey revealed that more than 50% of the diseases were of infectious origin, followed by hair follicle and sebaceous gland disorders. Socioeconomic status and environmental factors may be responsible for this.
Keywords: Age Factors; Classification; Epidemiology; Kožne bolezni; Skin Diseases; Starostni faktorji; Tunisia; Tunizija